Comparative study of the loss of vitamin C in chalarina (Casimiroa edulis) by four methods of dehydration - Castañeda, Judith (2010)
The aim of this study was to compare the loss of chalarina vitamin C after applying four methods of dehydration: vacuum osmotic dehydration combined with convective drying, convective drying, osmotic dehydration combined with vacuum freeze-drying, and freeze-drying. The fresh chalarina was fitted into cubes of 1 cm; we determined the vitamin C content and other chemical properties of the pulp. The powders were characterized: vitamin C, moisture content, aw, density, angle of flow and compressibility. Fresh chalarina pulp has a vitamin C content of 29.75 mg/100g. Osmotic dehydration and vacuum reduced to 15.75 mg/100g this content; combined with convective drying is reached 9.31 mg/100g; if combined with freeze-drying is obtained 14.98 mg/100g. Applying convective drying was obtained only 7.05 mg of vitaminaC/100g chalarina powder, while by applying only freeze-drying was obtained 23.63 mg/100g. We conclude that the powder obtained by vacuum osmotic dehydration - convective drying has better physical and chemical characteristics of powders obtained with other methods of dehydration.